PELATIHAN PENINGKATAN EKONOMI PETANI JAMUR TIRAM DI GAMPONG ASAN KAREUNG KECAMATAN BLANG MANGAT KOTA LHOKSEUMAWE - Maisyuri Maisyuri; M. Taqdirul Alim; Lusi Dyana Hasra; Bobby Rahman; Mulia Andirfa; Al Qahar Al Qahar; Khairunnisa Khairunnisa (Asia-Pacific Journal of Public Policy, 2023)
Community empowerment can be defined as a social action in which residents of a community organize themselves to make collective plans and actions to solve social problems or meet social needs according to their abilities and resources. In reality, often this process does not emerge automatically, but grows and develops based on the interaction of the local community with outsiders or social workers either from a charitable or professional perspective. This activity aims to overcome the problems that are being faced by mushroom farmers to increase production yields, overcome problems related to business development which will be overcome by structuring the business management system that has been running. The training program to improve the economy of oyster mushroom farmers in Gampong Asan Kareung, Blang Mangat District, Lhokseumawe City can be held well and run smoothly in accordance with the activity plan that has been prepared even though not all mentoring participants have mastered the material presented. This activity was very well received as evidenced by the liveliness of the participants following the assistance well.